Success Team Strategy to Win Dewi Handayani in the 2018 Tanggamus Regent Election - Dilla Annisa; Wijayanto (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the strategy of Dewi Handajani's success team in winning the 2018 Tanggamus Regent Election. The research used a descriptive qualitative method through a field approach, with primary data in the form of interviews and secondary data from related documents. Informants were selected purposively to obtain in-depth information. Data were collected through free guided interviews and documentation, then analyzed using data reduction, presentation and verification techniques with triangulation to ensure validity. The results showed that Dewi Handajani's winning strategy refers to the concept of 4P political marketing, namely product, promotion, place, and price. The product strategy includes the introduction of the candidate's vision and mission through various media and props, such as stickers and billboards. The promotion strategy is carried out through social media, print, and direct door-to-door approach by the core team and volunteers. The place strategy utilizes the support base in 18 out of 20 sub-districts. The price aspect included economic spending, while the psychological price was not emphasized because Dewi Handajani is not a regional daughter. This strategy was effective, as evidenced by the 55.97% vote victory. The implications of this research show the importance of a combination of comprehensive political marketing strategies in building trust and electability of candidates amidst the challenges of local politics, as well as the relevance of a personal approach in increasing campaign effectiveness.